2015
DOI: 10.1200/jco.2014.58.0571
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Significance of NPM1 Mutations in the Absence of FLT3–Internal Tandem Duplication in Older Patients With Acute Myeloid Leukemia: A SWOG and UK National Cancer Research Institute/Medical Research Council Report

Abstract: A B S T R A C T PurposeYounger patients with acute myeloid leukemia (AML) harboring NPM1 mutations without FLT3-internal tandem duplications (ITDs; NPM1-positive/FLT3-ITD-negative genotype) are classified as better risk; however, it remains uncertain whether this favorable classification can be applied to older patients with AML with this genotype. Therefore, we examined the impact of age on the prognostic significance of NPM1-positive/FLT3-ITD-negative status in older patients with AML. Patients and MethodsPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 29 publications
6
102
2
Order By: Relevance
“… AML, acute myeloid leukaemia; FLT3 -ITD, FLT3 internal tandem duplication mutation; FLT3 -TKD, FLT3 tyrosine-kinase-domain mutation; MLL -PTD, MLL (KMT2A) partial tandem duplication; NA, not available; NK‑AML, normal‑karyotype acute myeloid leukaemia. * Inclusive of all karyotypes, except when noted; discrepancies between the mutational frequencies in younger (age <60 years) and elderly (age ≥60 years) patients with NK‑AML have been reported, when available. ‡ Ostronoff et al 148 used the age of >65 years as the cut‑point definition for ‘elderly’ patients. § The study by Schnittger et al 155 included only patients with intermediate-risk AML. ‖ Paschka et al 156 defined younger adult patients as those aged 18–61 years. ¶ Schlenk et al 27 analyzed CEBPA mutations in elderly patients with normal karyotypes only. …”
Section: Figurementioning
confidence: 99%
“… AML, acute myeloid leukaemia; FLT3 -ITD, FLT3 internal tandem duplication mutation; FLT3 -TKD, FLT3 tyrosine-kinase-domain mutation; MLL -PTD, MLL (KMT2A) partial tandem duplication; NA, not available; NK‑AML, normal‑karyotype acute myeloid leukaemia. * Inclusive of all karyotypes, except when noted; discrepancies between the mutational frequencies in younger (age <60 years) and elderly (age ≥60 years) patients with NK‑AML have been reported, when available. ‡ Ostronoff et al 148 used the age of >65 years as the cut‑point definition for ‘elderly’ patients. § The study by Schnittger et al 155 included only patients with intermediate-risk AML. ‖ Paschka et al 156 defined younger adult patients as those aged 18–61 years. ¶ Schlenk et al 27 analyzed CEBPA mutations in elderly patients with normal karyotypes only. …”
Section: Figurementioning
confidence: 99%
“…62 A study of older AML patients suggested that NPM1(+)/FLT3-ITD-(−) confers a favourable prognosis for patients with AML of ages 55-65 years but not in those of age >65 years. 63 Recent recommendations from the ELN include a revised version of the risk stratification according to genetics including the allelic ratio ( Table 1). 3 …”
Section: Concurrent Mutationsmentioning
confidence: 99%
“…9,10 High-risk karyotypes are more common in older patients with AML, and even markers associated with a more favorable prognosis in younger individuals, such as inv (16) or t (8;21), are not favorable in patients more than 65 years of age. 11 Similarly, mutations favorable in younger patients, including those in NMP1, are not associated with a better prognosis in older individuals, 12 and 5-year survival in patients with the FLT3 ITD mutations who are older than 55 years is less than 10%, compared with 20% in younger individuals. [12][13][14] MDS advances more rapidly in older patients: the median life expectancy with intermediate risk MDS by IPSS-R (International Prognostic Scoring SystemRevised) criteria is 5.2 years in patients aged 65 years or younger compared with 2.6 years in older patients.…”
Section: Affluent Health-care Systems and Aging Populationsmentioning
confidence: 99%
“…11 Similarly, mutations favorable in younger patients, including those in NMP1, are not associated with a better prognosis in older individuals, 12 and 5-year survival in patients with the FLT3 ITD mutations who are older than 55 years is less than 10%, compared with 20% in younger individuals. [12][13][14] MDS advances more rapidly in older patients: the median life expectancy with intermediate risk MDS by IPSS-R (International Prognostic Scoring SystemRevised) criteria is 5.2 years in patients aged 65 years or younger compared with 2.6 years in older patients. 15 Age is the most potent adverse risk factor for patients with low-risk MDS in the MD Anderson scoring system.…”
Section: Affluent Health-care Systems and Aging Populationsmentioning
confidence: 99%